2019
DOI: 10.1177/1558944719849115
|View full text |Cite
|
Sign up to set email alerts
|

Neuroma Management: Capping Nerve Injuries With an Acellular Nerve Allograft Can Limit Axon Regeneration

Abstract: Background: Management of painful neuromas continues to challenge clinicians. Controlling axon growth to prevent neuroma has gained considerable traction. A logical extension of this idea is to therefore develop an approach to control and arrest axon growth. Given the limits in axonal regeneration across acellular nerve allografts (ANAs), these constructs could provide a means to reliably terminate axon regeneration from an injured nerve. The purpose of this study was to determine if attaching an ANA to an inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The use of ANAs for peripheral nerve reconstruction has recently spread, as shown by recent medical literature. Isaacs and coworkers [14] have implanted ANAs in combination with nerve connectors in rats and Hong and coworkers [15] have successfully tested ANAs in an animal setting for such a challenging problem as painful neuroma. ANAs were also efficaciously employed in a clinical context for human trigeminal nerve [16] and upper extremities reconstructions [17] and they have been successfully utilized for brachial plexus reconstruction by Li and collaborators [18].…”
Section: Discussionmentioning
confidence: 99%
“…The use of ANAs for peripheral nerve reconstruction has recently spread, as shown by recent medical literature. Isaacs and coworkers [14] have implanted ANAs in combination with nerve connectors in rats and Hong and coworkers [15] have successfully tested ANAs in an animal setting for such a challenging problem as painful neuroma. ANAs were also efficaciously employed in a clinical context for human trigeminal nerve [16] and upper extremities reconstructions [17] and they have been successfully utilized for brachial plexus reconstruction by Li and collaborators [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that silicone tubes, collagen tubes, microcrystalline chitosan, and PRGD/PDLLA conduits can achieve satisfactory effects in preventing traumatic neuroma formation. [22][23][24][25][26][27][28] Hong et al 29 found that acellular nerve allografts (ANAs) attached to the proximal end of an injured nerve can limit axon growth in a controlled manner, indicating that the use of ANAs as a tool to control neuroma formation may be a viable clinical option. In addition, Zhou et al 11 found that the application of a nanofibrous scaffold consisting of aligned silk fibroin blended with poly(l-lactic acid-co-caprolactone) activated the RhoA/ROCK signaling pathway, which contributed to the prevention of traumatic painful neuroma formation because of its suppressive effect on axon regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the short-term follow-up period. Even though evaluation periods of 8 weeks or less have been set as the endpoint in different studies on traumatic neuromas, 11,25,29,39,40 a longer evaluation period for painful neuromas may be better. This is not only because neuroma-related pain is a chronic problem but also because it is necessary to evaluate the long-term effects after the gelatin blocker completely degrades.…”
Section: Discussionmentioning
confidence: 99%
“…The use of acellular nerve allografts (ANA) as a cap to limit axon regeneration has also been investigated for the management of neuroma pain. 34 Proof of concept was established in a rat model demonstrating that ANAs attached to the proximal end of an injured nerve limited axon growth in a controlled matter, resulting in a lack of neuroma formation. In addition, the extent of axon growth from the injured nerve into the ANA was dependent on the ANA length.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the extent of axon growth from the injured nerve into the ANA was dependent on the ANA length. 34 Clinically, this would allow the surgeon to reliably terminate the axonal regeneration from an injured nerve by selecting an appropriate length ANA. This provides a less technically challenging, but more costly option for neuroma management.…”
Section: Discussionmentioning
confidence: 99%